Clinical presentation of human leptospirosis in febrile patients: Urabá, Colombia. - Pablo Uribe-Restrepo; Janeth Perez-Garcia; Margarita Arboleda; Claudia Munoz-Zanzi; Piedad Agudelo-Florez (PLoS Neglected Tropical Diseases)
Background Leptospirosis is responsible for various clinical syndromes, classically linked with fever and acute kidney injury. Methodology/principal findings A prospective multicenter observational study was conducted in six health institutions in the region of Urabá, Colombia. Enrollment was based on leptospirosis-compatible clinical syndrome and a positive preliminary serological test, with PCR used to confirm the disease. Clinical data were collected using a standard questionnaire at enrollment, complemented with a review of clinical records. A total of 100 patients were enrolled, 37% (95% CI 27.0-46.9%) had a positive PCR result confirming acute leptospirosis. The most frequent symptoms in patients with a positive PCR test were headache (91.9%; 34/37), chills and sweating (80.6%; 29/37), nausea (75%; 27/37), dizziness (74.3%; 26/37), vomiting (61.1%; 22/37), congestion (56.8%; 21/37), and conjunctival suffusion (51.4%; 19/37). The frequency of clinical signs classically described in leptospirosis was low: jaundice (8.3%; 3/36) and anuria/oliguria (21.6%; 8/37). An increased neutrophile percentage was reported in 60.6% (20/33) of patients. The presence of complications was 21.6% (8/37), with pulmonary complications being the most frequent (75.0% 6/8). One confirmed case died resulting in a fatality of 2.7% (95% CI 0.5-13.8). Conclusions/significance Leptospirosis should be considered within the differential diagnoses of an undifferentiated acute febrile syndrome. Leptospirosis presents diagnostic challenges due to limitations in both clinical and laboratory diagnosis thus it is important to improve understanding of disease presentation and identify signs and symptoms that might help differentiate it from other causes of febrile illness.